2016
DOI: 10.1159/000441185
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Caloric Intake Might Override the Prosteatotic Effects of the <b><i>PNPLA3</i></b> p.I148M and <b><i>TM6SF2</i></b> p.E167K Variants in Patients with Fatty Liver: Ultrasound-Based Prospective Study

Abstract: Background: The adiponutrin (PNPLA3) p.I148M and transmembrane 6 superfamily member 2 (TM6SF2) p.E167K variants represent risk factors for non-alcoholic fatty liver disease (NAFLD). In this study, we assessed the effects of caloric restriction on liver phenotypes in NAFLD patients in relation to the PNPLA3 and TM6SF2 genotypes. Methods: We genotyped both variants in 143 individuals with NAFLD (55 females, age 18-74 years) and 180 controls (85 females, age 33-66 years). Liver steatosis was assessed using the ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
1
22
0
1
Order By: Relevance
“…1 . Characteristics of studies included in the meta-analysis of liver enzymes in NAFLD 12 16 19 20 21 22 23 24 25 26 27 ( n = 11) are shown in Table 1 , while those included in the meta-analysis of patients with viral hepatitis 15 16 17 18 ( n = 4) are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 . Characteristics of studies included in the meta-analysis of liver enzymes in NAFLD 12 16 19 20 21 22 23 24 25 26 27 ( n = 11) are shown in Table 1 , while those included in the meta-analysis of patients with viral hepatitis 15 16 17 18 ( n = 4) are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies included in the meta-analysis were hospital-based 15 16 17 18 19 20 21 22 23 24 27 , while the other three were population-based 12 25 26 studies; three studies included pediatric population 20 21 25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Krawczyk et al reported that TM6SF2 variant as well as PNPLA3 variation did not impair the response to low-calorie four-month dietetic intervention in 143 NAFLD patients [71]. Indeed, the dietary interventions improved phenotypic traits, steatosis and ALT concentrations independently of the presence of these two variants [71]. Finally, Dongiovanni et al revealed that the rs58542926 TM6SF2 variant did not impact on the beneficial effect of statins administration in NAFLD patients [72], opening the possibility to treat T allele carriers with statins to ameliorate liver damage, even if the lipid profile of these patients does not encourage this therapeutic strategy [67].…”
Section: Tm6sf2: Two Sides Of the Same Coinmentioning
confidence: 99%
“…However, Krawczyk et al reported that TM6SF2 variant as well as PNPLA3 variation did not impair the response to low-calorie four-month dietetic intervention in 143 NAFLD patients [71]. Indeed, the dietary interventions improved phenotypic traits, steatosis and ALT concentrations independently of the presence of these two variants [71].…”
Section: Tm6sf2: Two Sides Of the Same Coinmentioning
confidence: 99%